NiTi-Layered double hydroxides nanosheets as efficient photocatalysts for oxygen evolution from water using visible Light - Zhao, Y; Li, B; Wang, Q; Gao, W; Wang, C; Wei, M; Evans, D; Duan, X; O'Hare, D (2014)
NiTi-Layered double hydroxides (LDH) nanosheets with lateral dimensions in the range 30-60 nm have been prepared using a reverse microemulsion method. These materials exhibit excellent photocatalytic activity (∼2148 μmol g-1 h-1) for oxygen evolution from water using visible light. The quantum yield was found to be 65.0% and 20.0% using monochromatic irradiation at 400 and 650 nm respectively. This journal is © The Royal Society of Chemistry 2014.